2018
DOI: 10.1038/s41598-018-21236-w
|View full text |Cite
|
Sign up to set email alerts
|

One-step noninvasive prenatal testing (NIPT) for autosomal recessive homozygous point mutations using digital PCR

Abstract: Previously, we introduced a noninvasive prenatal testing (NIPT) protocol for diagnosing compound heterozygous autosomal recessive point mutations via maternal plasma DNA and simulated control genomic DNA sampling based on fetal DNA fraction. In our present study, we have improved our NIPT protocol to make it possible to diagnose homozygous autosomal recessive point mutations without the need to acquire fetal DNA fraction. Moreover, chi-squared test and empirical statistical range based on the proportion of mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…[6][7][8][9] Both low throughput methods (eg, real-time PCR) and high throughput technologies (eg, Next-Generation Sequencing [NGS]) have been tested on cffDNA with different performances. [10][11][12][13] It is believed that detection of paternal mutations with NGS can be readily achieved with high sensitivity and specificity, 14 while detection of maternal allele in cffDNA is more challenging mainly due to maternal interference. Thus, a new generation of noninvasive prenatal testing/diagnosis methods, which can accurately detect diverse genetic abnormalities, are needed for pregnant women from families with risks of monogenic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Both low throughput methods (eg, real-time PCR) and high throughput technologies (eg, Next-Generation Sequencing [NGS]) have been tested on cffDNA with different performances. [10][11][12][13] It is believed that detection of paternal mutations with NGS can be readily achieved with high sensitivity and specificity, 14 while detection of maternal allele in cffDNA is more challenging mainly due to maternal interference. Thus, a new generation of noninvasive prenatal testing/diagnosis methods, which can accurately detect diverse genetic abnormalities, are needed for pregnant women from families with risks of monogenic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it difficult to evaluate the clinical performance, resulting in large ranges of confidence intervals and low sensitivity compared to other studies. 39,40 Although our method was less complicated comparing with previous methods, 41,42 our method could not provide a full fetal genotype interpretation, and consequently was only suitable for analyzing de novo mutations and paternal alleles. Nonetheless, as a proofof-concept study, the data collected from 68 pregnancies demonstrated the stability and repeatability of TAGs-seq in simultaneously generating low-pass whole-genome data and high-depth data of target genes.…”
Section: Discussionmentioning
confidence: 98%
“…Some of these methods, namely, droplet digital PCR, may be available in the near future for use in noninvasive prenatal testing. 23,24…”
Section: Discussionmentioning
confidence: 99%